COMPARATIVE ANALYSIS OF VIRTUAL COMMUNICATION CHANNELS USED BY PET SHOP CHAINS - Angelica Batista da Silva, Camila; Nanni, Henrique Cesar; Pereira , Ludmilla de Santana (Revista Interface Tecnológica, 2023)
The pet shop trade continues to grow, even after the pandemic. The number of pets and the attachment of humans to their pets is another growing factor. The use of more effective communication channels is essential for companies to get closer to their target audience. The objective of this research is to analyze and compare the main communication channels with an emphasis on the virtual ones in the three largest companies in the “Pet Shop” sector in Santos. The premise is to verify the best tools, as an instrument to improve the relationship and retain customers. This is a study with an exploratory approach. The necessary elements for comparative analysis were searched on websites and social networks. The results show the main means of communication used by companies to transmit informational content, the main ones being: TikTok, Instagram and YouTube. However, it is clear to say that virtual channels carry various types of messages and are part of the marketing strategies of pet shop companies.
Keywords: Pet shop; Communication channels; Social media